Potensi Pengolahan Dan Pengelolaan Budidaya Rumput Laut (Kappaphycus alvarezii) Di Wilayah Provinsi Kalimantan Utara - Zainuddin, Zainuddin (Politeknik Negeri Ketapang, 2023)
North Kalimantan province states that the average seaweed productivity from 2015-2019 reached 256,900.5 tons/hectare/year. North Kalimantan province is one of the seaweed producing locations with the characteristics of the archipelago-shaped region. The purpose of this research to know the potential processing of seaweed cultivation in the region of North Kalimantan Province, The method used for data collection in this study is the survey method, the data used in the research in the form of secondary data where the data is in the form of data obtained from literature studies, research results, institutions and related agencies that support the research, data analysis used in this study in the form of descriptive analysis. Based on the results obtained from research shows that the productivity of seaweed cultivation in North Kalimantan is still very low which is only 311,037 tons/year. The low cultivation of seaweed in North Kalimantan Province due to limited accessibility and production facilities is mentioned, causing the development of seaweed cultivation to be not optimal both in quantity and quality, this is due to non-optimal production support facilities thus reducing production capacity, as well as the marketing of products that are not wide so that the potential for sales is less optimal